A Digital Signal Processing Approach for the Finite Difference Time Domain Simulations of Graphene Nanomaterial - Ramadan, Omar (IEEE, 2019)
In this paper, the digital signal processing algorithms developed for digital filters are used in the finite difference time domain (FDTD) simulations of the dispersive Graphene nanomaterial. In the presented formulation, the Graphene dispersion is implemented in the FDTD algorithm by using the bilinear transformation (BT) technique. In addition, the root-locus method is used for studying the stability of the implementation and it is shown that the standard non-dispersive FDTD time step stability constraint is preserved. Numerical example is included to validate the accuracy of the presented formulation.
IEEE Jordan International Joint Conference on Electrical Engineering and Information Technology (JEEIT) -- APR 09-11, 2019 -- Amman, JORDAN
Keywords: Graphene nanomaterial; digital signal processing (DSP); finite difference time domain (FDTD); root-locus stability analysis